Evaluating the reproducibility of research in obstetrics and gynecology. (February 2022) - Rauh, Shelby; Bowers, Aaron; Rorah, Drayton; Tritz, Daniel; Pate, Heather; Frye, Lance; Vassar, Matt
Abstract: Objective: Reproducibility is a core tenet of scientific research. A reproducible study is one where the results can be recreated by using the same methodology and materials as the original researchers. Unfortunately, reproducibility is not a standard to which the majority of research is currently adherent. Methods: Our cross-sectional survey evaluated 300 trials in the field of Obstetrics and Gynecology. Our primary objective was to identify nine indicators of reproducibility and transparency. These indicators include availability of data, analysis scripts, pre-registration information, study protocols, funding source, conflict of interest statements and whether or not the study was available via Open Access. Results: Of the 300 trials in our sample, 208 contained empirical data that could be assessed for reproducibility. None of the trials in our sample provided a link to their protocols or provided a statement on availability of materials. None were replication studies. Just 10.58% provided a statement regarding their data availability, while only 5.82% provided a statement on preregistration. 25.85% failed to report the presence or absence of conflicts of interest and 54.08% did not state the origin of their funding. Conclusion: In the studies we examined, research in the field of Obstetrics and Gynecology is not consistently reproducible and frequently lacks conflict of interest disclosure. Consequences of this could be far-reaching and include increased research waste, widespread acceptance of misleading results and erroneous conclusions guiding clinical decision-making.